Cloud atlas : a novel - Mitchell, David (David Stephen) (New York : Random, 2004)
Recounts the connected stories of people from the past and the distant future, from a nineteenth-century notary and an investigative journalist in the 1970s to a young man who searches for meaning in a post-apocalayptic world.
Accelerated Reader AR
Keywords: Fate and fatalism -- Fiction; Reincarnation -- Fiction; Fantasy fiction